The Confédération des syndicats nationaux (CSN), the Idea of Independence, and the Sovereigntist Movement, 1960-1980 - Guntzel, Ralph (Labour/Le Travailleur, 1993)
During most of the 1960s, the CSN was both an advocate of provincial autonomy and a defender of federalism. In the late 1960s and early 1970s, however, a majority of its militants came to favour separatism. In 1980, the CSN gave its critical approval to a yes vote in the referendum. Yet the labour union central did not officially endorse independence, mostly because its leadership feared internal divisions and disaffiliations. In addition, the CSN expressed its disappointment with the governmental record of the Parti québécois which had come to power in 1976.